DOES THE DIGITAL GENERATION COMPREHEND BETTER FROM THE SCREEN OR FROM THE PAPER?: A META-ANALYSIS - Öztop, Feyyaz; Nayci, Ömer (International Online Journal of Education and Teaching, 2021)
This research was carried out to determine whether the comprehension level differs according to the reading environment by examining the studies comparing the comprehension level according to reading from the screen and from the paper by using meta-analysis method. Meta-analysis method was used in this research. The data of the study were obtained from 12 studies (29 comparisons). All of these studies are studies in which Turkish texts are used in reading. The analysis of the obtained data was carried out using the Comprehensive Meta-Analysis software. In the interpretation of the studies, random effects model was taken as basis. As a result of the analyses performed, a significant and medium effect size (g=-0.423, p=0.003) was found in favor of reading from the paper. Therefore, this result shows that comprehension achievement is higher in reading from the paper than reading from the screen. In addition, it was determined that the effect sizes did not differ significantly according to the publication year, grade level, text type and digital tool. It is recommended to perform studies on improving the screen interface and screen reading skills.